Communication and Nigeria’s Southern Women's Capacity Development for Financial Inclusion: An Assessment of Access Bank's Womenpreneur Pitch- a-ton - Titilayo Remilekun Osuagwu, Ph.D (Genius Journals, 2024)
Sustainable development of a society requires the participation of all genders in all spheres of life. However, there is a lack of capacity development initiatives for engendering women's sustainable financial inclusion. It is given that communicating financial inclusion programmes will increase women's participation. Hence this study leveraged the elaboration likelihood theory of persuasion to examine the extent of women's awareness of the financial capacity development initiative known as Access Bank’s Womenpreneur Pitch-a-ton. It also investigated sources of awareness and the extent of influence of the programme on the financial inclusion of Southern women. The study utilised mixed methods; survey and in-depth interview. Three hundred and eightyfour (384) women were purposively selected for the study. The study's findings demonstrated a lack of awareness of the initiative among the majority of the respondents, sources of awareness ranged from social media, emails, radio and Television. The majority of those who were aware said the programme motivated them for financial inclusion. The study concluded that awareness about "Access Bank Womenpreneur Pitch-a-ton" was low even though it was increasing urban women's visibility in the financial sector. The study recommended, among others, that Access Bank should broaden the communication arsenals for creating awareness about the capacity development programme to include interpersonal and traditional channels
Keywords: Capacity Development; Communication; Financial Inclusion